Nanoparticle Preparation of Pentagamavunon-0 Using Medium Viscous Chitosan Matrix Cross Linked by Sodium Tripolyphosphate Through Ionic Gelation Mechanism as Anti-Inflammatory Candidate - Adhyatmika Adhyatmika; Ronny Martien; Hilda Ismail (Majalah Farmaseutik, 2017)
Pentagamavunon-0 (PGV-0, abbreviated), a curcumin analogue with chemical structure as 2,5-bis(4’-hydroxy-3’-methoxybenzilidin)cyclopentanone, has proven to have anti-inflammatory activity and non-ulcerogenic. However, orally PGV-0 has low bioavailability because of its low solubility. One of the strategy to improve PGV-0 solubility in order to increase bioavailability is using nanoparticle carrier. The aim of the study is to formulate chitosan-PGV-0 nanoparticles through ionic gelation mechanism cross-linked by tripolyphosphate. PGV-0 nanoparticle produced was then characterized for its particle size, morphology, zeta potential, entrapment efficiency, and stability against artificial gastric and intestinal fluids (AGF and AIF). PGV-0 nanoparticle was tested for its anti-inflammatory activity by carrageenan induced inflammatory method, and its enzymatic affinity against enzyme cyclooxygenase (COX)-1 and COX-2. Chitosan-PGV-0 nanoparticles were formulated in the combination of 0,05% PGV-0, 0,05% medium-viscous chitosan and 0,002% TPP. The nanoparticles were 144,37 + 17,41 nm amorphous particles. Amount of PGV-0 entrapped was 99,40 + 0,08 % with +3,8 + 0,27 mV in zeta potential. Stability study in AGF and AIF was shown that 99,64-99,74 % (AGF) and 99,54-99,69 % (AIF) of PGV-0 remains in nanoparticles. Chitosan-PGV-0 nanoparticles at 5 mg/kg body weight was obtain 35,47 % anti-inflammatory activity and has found to have self-affinity against COX enzyme, relatively selective to COX-2.